Older Women’s Loneliness and Depression Decreased by a Reminiscence Program in Times of COVID-19 - Pinazo-Hernandis, Sacramento; Sales, Alicia; Martinez, Dolores (Frontiers in Psychology, 2022)
The confinement caused by the current COVID-19 pandemic protects physical health, but in turn, has a long-lasting and far-reaching negative psychosocial impact; anxiety, stress, fear and depressive symptoms. All of these have a particular impact on vulnerable older people, putting them at serious risk of loneliness. Women report feeling lonelier than men, affecting women to a greater extent. The present study aims to analyze the efficacy of an integrative reminiscence intervention in older women living in nursing homes to reduce the effects of loneliness and depression after COVID-19. 34 older women living in nursing homes are included into study and were divided into intervention group (N= 14) and control group (N= 20). Results showed a significant reduction in perception of loneliness, anxiety, depression and better positive affects, after the intervention. The pandemic has not yet finished and the most affected group has been the people living in nursing homes. These results show the need for evidence of interventions that can help the recovery of these people who have been so affected. The effects of loneliness during confinement and its psychological effects can be mitigated through such programs.